Pengaplikasian Model Bioekonomi Clarke Yoshimoto Pooley pada Sumberdaya Ikan Tenggiri (Scomberomorus commerson) yang didaratkan di Pelabuhan Perikanan Samudra Kutaraja Aceh - Agus Naufal; Rizki Ramazan; Faisal Syahputra; Mukhlis Mukhlis; Azwar Thaib; Teuku Faizul Anhar; Elfa Yeni (Center for Research and Community Service (LPPM) University of Abulyatama, 2024)
Penelitian ini bertujuan untuk menilai sumberdaya dan menganalisis tingkat Overexploitation of fishery resources with an open access system is still a serious threat because it leads to reduced fish stocks. This research aims to assess resources and analyze the level of degradation and depreciation of mackerel fish resources landed in Kutaraja Aceh Fishing Port using the Clarke Yoshimoto Pooley (CYP) bioeconomic model approach. The methods in this research include standardization of fishing gear using the fishing power index, sustainable potential analysis using the CYP model which is used to assess the sustainability of mackerel fish resources, degradation analysis and depreciation analysis to see the extent of depreciation of fishery resources. The results of the analysis show that the actual production of mackerel is 4.07 tons/year, which exceeds the Maximum Sustainable Yield (MSY) production of 3.3 tons/year. The actual fishing effort also reached 17,137 trips/year while the sustainable fishing effort (effort MSY) was only 6,351 trips/year. This value shows that the Mackerel fish resource has experienced overfishing both in terms of production and fishing effort. During the analysis period, the mackerel fish resource had experienced depreciation because it had exceeded the threshold (0.5) with an average depreciation coefficient of 0.989. However, mackerel fish did not show degradation of mackerel fish resources, namely 0.458, which was still below the threshold (0.5). However, this figure has almost exceeded the threshold so it deserves special attention from the government so that the mackerel fish resources landed at the Kutaraja Aceh Fishing Port will remain sustainable.